The Relationship between Intellectual Capital and Software Sector Performance in Malaysia - Pee, Ding Liang (2014)
In this age’s new economy, intellectual or intangible resources has become very valuable and has been the unique resource that firms around the globe continually tap into in order to find success. Intellectual resources allow new inventions and innovations on existing technologies and knowledge. Such resources has reshape the world into the new era of information age which operates around speed of information that is based on high tech electronics infrastructure. The new economy relies on such infrastructure as backbone as well. The Malaysian economy relies on the same backbone as it is part of the global economy. Hence, it is crucial for the government to take on initiatives to strengthen the backbone of the economy so that the economy can thrive. Knowledge is then the key element in doing so. Therefore the aim of this study is to identify the relationship between intellectual capital, namely Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE), and Structural Capital Efficiency (SCE) on software sector performance, specifically Market to Book ratio (MB), Return on Assets (ROA), Return on Equity (ROE), and Revenue Growth (RG). This follows the model developed by Ante Pulic in 1998 of Value Added Intellectual Coefficient (VAIC). The data of this study covers 24 publicly listed software firms over 7 years period from year 2006 to year 2012. Partial Least Squares regression analysis is used to analyze the model. The result suggest that there is weak overall relationship of intellectual capital towards software sector firm performance. HCE has shown to have a positive significant relationship towards all 4 proxies.